Kekerasan dan Pemerasan Perempuan Pekerja Seks Komersial dalam Aplikasi MiChat: Suatu Analisis Foucaultian - Sanjani, Moh. Ruslan Aditiya (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
The rapid rise of internet communication has transformed interactions, including business, relationships, and even the search for commercial sex through platforms like MiChat. This study explores violence, such as intimidation, coercion, and abuse, alongside exploitation, including blackmail and forced payments, within this digital landscape. Using Foucaultian perspective on power and resistance, it highlights how digital technology becomes a battleground for power dynamics in the sex industry. Employing qualitative methods, the research examines sex workers using MiChat as a social and economic platform through observations, interviews, and documentation. Findings reveal that while these workers gain autonomy in their profession, they remain susceptible to exploitation and violence from clients. However, sex workers resist these oppressions, illustrating a struggle for agency. Power dynamics emerge as clients use financial leverage and violence, whereas sex workers, particularly women, counteract these controls to reclaim their autonomy.